(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze the epidemiological profile of tuberculosis cases between 2010 and 2018. It is an ecological study, of a descriptive nature and with a quantitative approach, using secondary data, in which an epidemiological research of cases of TB in the municipality of São Luís and in the state of Maranhão from 2010 to 2018. Data were collected on the DATASUS website, from SINAN. The variables analyzed were: year of diagnosis, notification state and municipality, age group, sex and education. An increasing trend was identified, with 2018 (n = 1,288) being the most incident year, the highest number of TB cases was reported in the state of Maranhão, followed by the years 2017 (n = 1,127) and 2016 (n = 1,092). Regarding the level of education, there is a predominance (19.1%) in people between the 5th and 8th grades of elementary school, followed by those between the 1st and 4th grades of Elementary School. With regard to TB cases by sex, the largest number of cases occurred in males (n = 6,133). Regarding the age group, a higher prevalence was observed between 20-39 years (n = 4,495), followed by the 40-59 age group (n = 2,689).